1984
DOI: 10.1128/aem.47.5.979-985.1984
|View full text |Cite
|
Sign up to set email alerts
|

Phage Resistance in a Phage-Insensitive Strain of Streptococcus lactis : Temperature-Dependent Phage Development and Host-Controlled Phage Replication

Abstract: Streptococcus lactis ME2 is a dairy starter strain that is insensitive to a variety of phage, including 418. The efficiency of plating of 418 on ME2 and Ni could be increased from <1 x 10-9 to 5.0 x 10-2 and from 7.6 x 10-7 to 2.1 x 10-2, respectively, when the host strains were subcultured at 40°C before plating the phage and the phage assay plates were incubated at 40°C. Host-dependent replication was demonstrated in Ni at 30°C and in Ni and ME2 at 40°C, suggesting the operation of a temperature-sensitive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 21 publications
(25 reference statements)
1
17
1
Order By: Relevance
“…These mechanisms include plasmid-induced interference with phage adsorption, restriction and modification of phage, and a heat-sensitive mechanism that suppresses the burst size of infecting phage (Hsp +). The mechanisms acted cooperatively to confer a phage-insensitive state to S. lactis ME2 [36]. However, similar to pNP40, phage resistance at each of the three levels was inoperative following growth of the culture at 40°C.…”
Section: Plasmid Ptr2030mentioning
confidence: 96%
See 3 more Smart Citations
“…These mechanisms include plasmid-induced interference with phage adsorption, restriction and modification of phage, and a heat-sensitive mechanism that suppresses the burst size of infecting phage (Hsp +). The mechanisms acted cooperatively to confer a phage-insensitive state to S. lactis ME2 [36]. However, similar to pNP40, phage resistance at each of the three levels was inoperative following growth of the culture at 40°C.…”
Section: Plasmid Ptr2030mentioning
confidence: 96%
“…In the prototype phage-insensitive strain, S. lactis ME2 [28,36], curing of pME0030 resulted in increased phage adsorption of four heterologous phages. In one case, the degree of phage adsorption correlated with the plaquing efficiencies for phage 18 on S. lactis ME2 (EOP < 10 -9 at 40% adsorption) and the pME0030-cured variant, N1 (EOP = 10 -7 at 99.7% adsorption).…”
Section: Plasmid-directed Interference With Phage Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Watanabe et al [76] have suggested that two types of adsorption can exist; irreversible adsorption which can lead to infection, and reversible adsorption, which does not. It is impossible to distinguish between the two forms of adsorption on the basis of standard adsorption assays, it may 94 be that a new definition is required for insensitivity due to the failure of phage to initiate an infection by injecting its DNA after adsorption. "Injection blocking' is one possible phenotypic designation.…”
Section: Prelention Of Phage Injectionmentioning
confidence: 99%